REWASHING DALAM PEMELIHARAAN ARSIP FILM DI ARSIP NASIONAL REPUBLIK INDONESIA (ANRI) - , IGNATIUS EKO B ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Final report titled \"Rewashing in The Maintenance Film Archive at the National Archives of the Republic of Indonesia\" is the result of Field Work Practice held at the National Archives of the Republic of Indonesia. This report aims to determine, add insight and dig deeper into the film archive maintenance. In addition, to compare between the theory learned during lectures with the situation on the ground. The discussion in this report starts from the basic concept of the film archive maintenance, damage to the film archives, film structure and the type, condition of disk space, tools and materials, as well as maintenance of the archive films. Maintenance records movies in a way rewashing using ultrasonic cleaner machine and manually with rewainder table. The methods used to obtain the data in this report is the first library method, this method is used to obtain references or sources obtained comparing library materials and library materials obtained comparing with theory and practice. Both methods of observation and participation in which the method is carried out by directly observing and participating in the maintenance of film archives in the National Archives of the Republic of Indonesia. The last method is the method of interview. In this method is used to obtain data from speakers who are competent in the maintenance movie image at the National Archives of the Republic of Indonesia. The conclusion of this final report that activity in the maintenance rewashing film archives in the National Archives of the Republic of Indonesia, covering internal and external destructive factors, and prevention as rewashing archive process. Rewashing activities at the National Archives of the Republic of Indonesia is done automatically or manually. Then adequate facilities are not comparable with existing human resources. Will eventually become an obstacle in the film archive maintenance activities.